RISK-TAKING COMPARISON OF ISLAMIC AND CONVENTIONAL BANKS DURING COVID-19 PANDEMIC: INDONESIAN CASE STUDY - Sudrajad, Oktofa Yudha; Saksono, Rafif Adit; Afgani, Kurnia Fajar; Kharohmayani, Desy (CENTRAL ASIA AND THE CAUCASUS, 2022)
Indonesia adopts a dual banking system that is Islamic and Conventional which operate sides-by-side. There are 96 Conventional and 14 Islamic banks in Indonesia. During a pandemic, both banks use their strategies to maintain their performance. During Global Financial Crisis (GFC), conventional banks' risk-taking was less inclined when they were faced with lower funding liquidity risk while Islamic Banks tend to be more careful in taking more risk. However, it is unknown what impact will it have on banks in Indonesia during the COVID-19 pandemic. Using Islamic and Conventional banks data in Indonesia, this research analyzed using panel data regression finds that the presence of COVID-19 pandemic affects conventional and Islamic banks' risk-taking behavior, and both banks' risk-taking behavior was found to be different. It is also found that banks’ size has a positive correlation with banks’ risk-taking.